2006
DOI: 10.1049/el:20062257
|View full text |Cite
|
Sign up to set email alerts
|

Long-period gratings in chalcogenide (As 2 S 3 ) rib waveguides

Abstract: Long-period gratings in highly nonlinear chalcogenide glass (As 2 S 3 ) rib waveguides are fabricated. A strong resonance of $17 dB depths and 3 dB width of $15 nm is obtained at a wavelength of 1525 nm by coupling the fundamental mode to the HE 02 mode in good agreement with theory. The 20 mm grating is produced by a simple shadow mask technique and has a pitch of L ¼ 80 mm. the Australian Research Council (ARC). The Centre for Ultrahighbandwidth Devices for Optical Systems is an ARC Centre of Excellence. K. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…2 Arsenic trisulphide ͑As 2 S 3 ͒, one of the most widely studied of the ChGs, has been used for all-optical devices in various forms -bulk glass, optical fiber, and recently planar waveguides. Our research group ͑CUDOS͒ has reported the fabrication of As 2 S 3 planar waveguides using thin film deposition and plasma etching, [3][4][5][6][7] and has achieved high performance NLO devices using those waveguides. [8][9][10][11][12][13][14][15] For NLO devices the propagation loss of the waveguide is a significant factor determining performance.…”
Section: Introductionmentioning
confidence: 99%
“…2 Arsenic trisulphide ͑As 2 S 3 ͒, one of the most widely studied of the ChGs, has been used for all-optical devices in various forms -bulk glass, optical fiber, and recently planar waveguides. Our research group ͑CUDOS͒ has reported the fabrication of As 2 S 3 planar waveguides using thin film deposition and plasma etching, [3][4][5][6][7] and has achieved high performance NLO devices using those waveguides. [8][9][10][11][12][13][14][15] For NLO devices the propagation loss of the waveguide is a significant factor determining performance.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn has allowed the design of long period gratings to couple the fundamental mode into a higher order mode at telecom wavelengths. Using a shadow mask technique we have achieved 17 dB, 15 nm (3 dB) wide band rejection at a wavelength of 1525 nm [46]. We have also demonstrated nonphotosensitive long period gratings based on As 2 Se 3 fiber using the micro-bend [47] and acousto-optic [48] techniques.…”
Section: Bragg Gratings and Long Period Gratingsmentioning
confidence: 87%
“…In addition, both As 2 S 3 and SiO 2 materials are available and cheap also they can implement in the practical fabrication. Recently, these materials are very attractive for ultrahigh bit-rate signal processing applications (Finsterbusch, Baker, Ta, Eggleton, Choi, & Madden, 2006;Luan, Pelusi, Lamont, Choi, Madden, Luther-Davies, & Eggleton, 2009). …”
Section: Design and Optimizationmentioning
confidence: 99%